2018
DOI: 10.14483/22487085.12422
|View full text |Cite
|
Sign up to set email alerts
|

Reverse mentoring and peer coaching as professional development strategies

Abstract: Presently, learning a foreign language is an essential academic requirement in several contexts, hence the importance and the need for effective teaching in this field at all educational levels starting with the first years of school. As a consequence, teaching and learning in elementary school is a key issue to success in the learner’s future language learning. However, at some public elementary schools in Colombia there are many factors that hinder this process. One of them is the fact that most of the teach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 16 publications
0
5
0
5
Order By: Relevance
“…Augustinienė and Čiučiulkienė claim that "effective reverse mentoring is based on the duality of roles and is always a twoway flow of learning which may be characterized as a boomerang effect" (p. 76). Likewise, Porras et al (2018) affirm that the relationship between in-service elementary school teachers and student-teachers in a reverse mentoring experience was strengthened because the attitude of both sides was open and collaborative. This concept is coherent with Murphy's (2012), who points out that mentoring facilitates reciprocal gains for those involved in terms of learning, growth, and development Therefore, these aspects are clearly related to changes in assumptions and participants' preconceived notions of themselves as mentors and mentees.…”
Section: Reverse Mentoringmentioning
confidence: 75%
See 1 more Smart Citation
“…Augustinienė and Čiučiulkienė claim that "effective reverse mentoring is based on the duality of roles and is always a twoway flow of learning which may be characterized as a boomerang effect" (p. 76). Likewise, Porras et al (2018) affirm that the relationship between in-service elementary school teachers and student-teachers in a reverse mentoring experience was strengthened because the attitude of both sides was open and collaborative. This concept is coherent with Murphy's (2012), who points out that mentoring facilitates reciprocal gains for those involved in terms of learning, growth, and development Therefore, these aspects are clearly related to changes in assumptions and participants' preconceived notions of themselves as mentors and mentees.…”
Section: Reverse Mentoringmentioning
confidence: 75%
“…This shows that being an English teacher at any school level requires not only a good command of the language, but also the use of a specific methodology. According to Porras et al (2018), "it is paramount that teachers be sufficiently qualified since they play an important role as facilitators of the teaching and learning process, equally, [they] are a source of input for their students, especially at the elementary level" (p. 170). For this reason, the reverse mentoring stage was beneficial for the in-service teachers since they became aware of the importance of possessing knowledge as regards how to teach English to children.…”
Section: Beliefs About Foreign Language Proficiencymentioning
confidence: 99%
“…A number of the articles published on reverse mentoring were not data-driven but were written using an original conceptual idea that provided a framework and opportunity for new research (Baily, 2009; Bolser and Gosciej, 2015; Boysen et al , 2016; Brinzea, 2018; Chaudhuri, 2019; Chaudhuri and Ghosh, 2012; Harvey et al , 2009; Lawrence, 2017; Morris, 2017; Murphy, 2012; Napier, 2006; Sanner-Stiehr and Vandermause, 2017; Zauschner-Studnicka, 2017). Few studies have been found to use a mixed-method approach to measure the effectiveness of reverse mentoring (Chen, 2018; Leedahl et al , 2019; Leh, 2005; Porras et al , 2018). The quantitative studies have been mainly descriptive using survey and cross-sectional research designs, quasi-experimental design and regression analysis (Biss and DuFrene, 2006; Chen, 2014, 2015; Hechl, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…actors pursuing the same goals and sharing a common temporality (Díaz-Vicario & Gairín Sallán, 2018). According to Porras et al (2018), teacher interactions promote reflective practice, as they question their own knowledge and learning process and find the best ways to encourage the professional development of their colleagues (Porras et al, 2018).…”
Section: The Professional Communitymentioning
confidence: 99%